Empowerment of women's group through the utilization of siwalan fruit - Dwi Novri Supriatiningrum; Arny Herawaty; Farah Amelia Vidiastuti (Community Empowerment, 2022)
Hendrosari Village is one of the siwalan fruit-producing villages. Old siwalan fruits are wasted because many siwalan fruit products are sold unripe or half ripe. The objective of this program is to produce food from old siwalan fruit to contribute in the development of the tourism industry in Hendrosari Village. Community service methods use socialization, demonstrations, practices, discussions, and evaluations. Innovation in food products using food processing technology allows for the production of ice cream and cookies from old siwalan fruit. 75 percent of the community was very excited to take part in this program and hoped that other innovations in the use of the highly valuable old siwalan fruit would be held.